AUDIT AWAL SISTEM INFORMASI PADA PT. X BERDASARKAN STANDAR CONTROL OBJECTIVES FOR INFORMATION AND RELATED TECHNOLOGY (COBIT 4.1) - Monica, Cindy; Santoso, Leo Willyanto; Yulia, Yulia (Institute of Research and Community Outreach - Petra Christian University, 2015)
PT. X is a company engaged in the field of iron and steel construction, located in Surabaya. Not easy for a large company with business processes that are also wide enough to carry out all processes in the company by way of the manual. This is because in the era of globalization, companies must be able to address the issues and changes that occur quickly and on target. Therefore, companies urgently need an integrated application. However, the factor that must be considered not only focuses on the acquisition of application systems needed by the company alone. But companies also need to focus on maintaining the quality of the application system. Because the application system useful to support and enhance the company's management in order to improve company performance and effectiveness in delivering services to the public. Therefore, the researcher wants to conduct the audit planning of application system for PT. X with analysis on the condition of IT at PT. X to determine the COBIT domains that need to be audited.